An introduction to the sociology of religion: classical and contemporary perspectives - Furseth, Inger (Ashgate, 2006)
Is it true that religion is weakening in modern times or are we facing religious resurgence? What is fundamentalism? How does it emerge and grow? Which role does religion play in ethnic and national conflicts? Is religion a fundamental driving force or do political leaders use religion for their own purposes? Do all religions oppress women? These are some of the questions addressed in this book. "An Introduction to the Sociology of Religion" provides an overview of sociological theories of contemporary religious life. Some chapters are organized according to topic. Other chapters offer brief presentations of classical and contemporary sociologists from Karl Marx to Zygmunt Bauman and their perspectives on social life, including religion. Throughout the book, illustrations and examples are taken from several religious traditions.